Indigo Carmine and 2,6-Dichlorophenolindophenol Removal Using Cetyltrimethylammonium Bromide-Modified Palm Oil Fiber: Adsorption Isotherms and Mass Transfer Kinetics - Ngaha, Marcel Cédric Deussi; Njanja, Evangéline; Doungmo, Giscard; Tamo Kamdem, Arnaud; Tonle, Ignas Kenfack (International Journal of Biomaterials, 2019)
In the present work, the usefulness of cetyltrimethylammonium bromide-modified palm oil fiber (CTAB-modified POF) for the removal of indigo carmine (IC) and 2,6-dichlorophenolindophenol (2,6-DCPIP) from aqueous solutions was investigated. Raw, NaOH-treated, and CTAB-modified POF were characterized by Fourier-transform infrared (FT-IR) spectroscopy, elemental analysis, thermogravimetric-hyperdifferential scanning calorimetric (TG-HDSC) analysis, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The adsorption studies of IC and 2,6-DCPIP were performed in batch mode using CTAB-modified POF. The results showed that equilibrium was attained after a contact time of 30 minutes for IC and 20 minutes for 2,6-DCPIP. The maximum capacity of adsorption was obtained at pH = 2. The capacity of adsorption considerably increased with modified biosorbents and with increasing initial concentration of dyes. The ionic strength favors the increasing adsorption capacity of IC and does not affect the adsorption capacity of 2,6-DCPIP. The percentage of adsorption increased with increasing mass of the biosorbents. The nonlinear regression of adsorption isotherms showed that Freundlich (r2 = 0.953; χ2 = 4.398) and Temkin (r2 = 0.986; χ2 = 1.196) isotherms are most appropriate to describe the adsorption of IC and 2,6-DCPIP on CTAB-modified POF, respectively. The maximum adsorption capacities determined by the Langmuir isotherm were 275.426 and 230.423 μmol·g−1 for IC and 2,6-DCPIP, respectively. The linear regression of adsorption kinetics was best described by the pseudo-second-order model (R2 ≥ 0.998). The diffusion mechanism showed that external mass transfer is the main rate controlling step. Desorption of the two dyes is favorable in the alkaline medium.